Legal Reasoning of the Constitutional Court Verdict Number 25/PUU-XX/2022 on the State Capital Law According to Social Justice Value - Achmad Miftah Farid Farid; Nanik Prasetyoningsih Nanik (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: This study analyzes the legal reasoning of the Constitutional Court judges in deciding the judicial review Number 25/PUU-XX/2022 against Law Number 3 of 2022 concerning the State Capital (Undang-Undang Ibu Kota Negara/State Capital Law), as well as analyzed based on social justice theory.  Methodology: This study uses a juridical-normative method through a statute approach and case studies. The method of analysis is carried out qualitatively, while the method of collecting legal materials is through documentary research. Results: An analysis of the Constitutional Court verdict concluded that the panel of judges considered that the State Capital Law was declared constitutional to the Constitution and rejected the review of the State Capital Law. The plaintiffs also did not have strong legal standing in the process of forming the State Capital Law. The judges had the opinion that all processes for establishing the State Capital Law met the formal and material requirements. Unfortunately, the Constitutional Court verdict has not fully met the value of social justice for society. Applications of this study: This research is expected to provide a contribution to constitutional law and provide scientific recommendations for the public in cases of judicial review at the Constitutional Court. Novelty/Originality of this study: The Constitutional Court’s verdict is final and binding, whether it fulfills the value of social justice or not. However, the constitutional value should be directly proportional to the value of justice for society. The Constitutional Court verdicts should have an equal proportion of justice for society and the government. Keywords: Constitutional Court Verdict; Constitutional; Legal Reasoning; Social Justice; State Capital Law.   ABSTRAK Tujuan: Kajian ini menganalisis pertimbangan hukum hakim konstitusi dalam memutus uji materil Nomor 25/PUU-XX/2022 terhadap Undang-Undang Nomor 3 Tahun 2022 tentang Ibu Kota Negara, serta dianalisis berdasarkan teori keadilan sosial.  Metodologi: Penelitian ini menggunakan metode yuridis-normatif melalui pendekatan undang-undang dan studi kasus. Metode analisis dilakukan secara kualitatif, sedangkan metode pengumpulan bahan hukum melalui penelitian dokumenter.  Hasil: Analisis putusan Mahkamah Konstitusi menyimpulkan bahwa majelis hakim menilai UU Ibukota Negara dinyatakan konstitusional terhadap UUD dan menolak pengujian UU Ibukota Negara. Para penggugat juga tidak memiliki legal standing yang kuat dalam proses pembentukan UU Ibukota Negara. Majelis hakim berpendapat bahwa semua proses pembentukan UU Ibukota Negara telah memenuhi syarat formil dan materil. Sayangnya, putusan MK belum sepenuhnya memenuhi nilai keadilan sosial bagi masyarakat.  Aplikasi penelitian ini: Penelitian ini diharapkan dapat memberikan kontribusi terhadap hukum tata negara dan memberikan rekomendasi ilmiah bagi masyarakat dalam perkara uji materil di Mahkamah Konstitusi.  Kebaruan/Orisinalitas: Putusan Mahkamah Konstitusi bersifat final dan mengikat, apakah memenuhi nilai keadilan sosial atau tidak. Namun, nilai konstitusi harus berbanding lurus dengan nilai keadilan bagi masyarakat. Putusan Mahkamah Konstitusi harus memiliki proporsi keadilan yang sama bagi masyarakat dan pemerintah.  Kata kunci: Putusan Mahkamah Konstitusi; Konstitusional; Penalaran Hukum; Keadilan sosial; Ibu kota Negara.